Development of Augmented Reality Learning Media To Enhance Elementary Students’ Conceptual Understanding of The Human Respiratory System In Science Learning - Ani Subekti; Sri Yamtina; M. Salimi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to develop and evaluate Augmented Reality (AR)-based interactive learning media designed to strengthen fifth-grade students' conceptual understanding of the human respiratory system. The study responds to a research gap in elementary science learning: previous AR studies have mostly emphasized media development, while fewer have integrated AR products with a structured instructional design and multistage classroom testing. This research employed a Research and Development (R&D) design using the ADDIE model. The product was tested through expert validation, a small-scale practicality test involving 10 students and one teacher, an intermediate feasibility trial involving 42 students, and an effectiveness test using a pretest-posttest control group design with 30 students in the control class and 35 students in the experimental class. Instruments consisted of expert validation sheets, teacher and student response questionnaires, observation notes, and conceptual understanding tests. Data were analyzed using Aiken's V, descriptive statistics, paired sample t-tests, effect size, and normalized gain (N-gain). The results showed that the media was highly valid, with Aiken's V values of 0.91 for material, 0.89 for media, and 0.87 for language. The practicality scores were also high, with 93.75% from the teacher and 88.40% from students. In the intermediate trial, students' mean score increased from 67.97 to 77.26, with a significant paired t-test result (t = -8.072; p < .001) and a large effect size (Cohen's d = 1.246). The effectiveness test showed that the experimental class obtained an N-gain of 0.75 (high category), whereas the control class reached only 0.07 (low category). These findings indicate that AR-based interactive media can make abstract respiratory system concepts more visible, interactive, and meaningful for elementary students.